A brief historical review of philosophical terminology in Arabic - Abdul Fatah Ibrahim, (Universiti Kebangsaan Malaysia, 1973)
Before Arabic spread to the neighbouring countries through the Islamic conquest, its vocabulary had already assimilated foreign words as a result of contact with neighbouring people. Following the Islamic conquest, Arabic took new forms unknown to the language before. The Mu'tazilite introduced a new style and philosophical terminology to meet the challenge of the time. In the Ummayad period, the form of secular prose was inspired, to a certain extent, by the Sasanid literature. The Sasanid cultures and traditions began to influence the Arab. The Abbasid period saw the beginning of the translation from Greek scientific and philosophical works into Arabic. The Caliphs themselves took the initiative and the learned men, irrespective of creeds and religious, rubbed shoulders together. The translators introduced terminology including the philosophical. They were not concerned with theology, mysticism or religious speculation because most of them were not Muslims and the chief interest of the Caliphs, who ordered the translation, was in medicine and philosophy. Since the Semitic languages are different from the peculiarities of Indo-European morphology and syntax, the translations considerably failed to convey the ideas precisely. Despite the difficulties, philosophical terminology grew up as the result of the flourishing and advancing stages of Islamic-Arabic literatures. The language expended, to meet the needs of the developments, from within by giving new meanings to old words or forming new words from old roots, and from without by arabisation.